Computational Logistics 4th International Conference, ICCL 2013, Copenhagen, Denmark, September 25-27, 2013, Proceedings - Pacino, Dario; Voß, Stefan; Jensen, Rune Møller (Theoretical Computer Science and General Issues, 2013)
This book constitutes the refereed proceedings of the 4th International Conference on Computational Logistics, ICCL 2013, held in Copenhagen, Denmark, in September 2013. The 19 papers presented in this volume were carefully reviewed and selected for inclusion in the book. They are organized in topical sections named: maritime shipping, road transport, vehicle routing problems, aviation applications, and logistics and supply chain management.